2018
DOI: 10.1093/abm/kax021
|View full text |Cite
|
Sign up to set email alerts
|

Is Resolution of Chronic Pain Associated With Changes in Blood Pressure-related Hypoalgesia?

Abstract: Background In healthy individuals, elevated resting blood pressure (BP) is associated with reduced pain responsiveness and lower temporal summation. Prior work indicates that this BP-related hypoalgesia is reduced in individuals with chronic pain. Purpose This study evaluated whether resolution of chronic pain was associated with greater BP-related hypoalgesia compared to nonresolution. Methods From a prospective sample of adolescents and young adults diagnosed with chronic functional abdominal pain an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…For example, Bruehl et al (1998) observed a small negative correlation between BP and clinical pain severity in patients with a pain duration between 6 and 14 months, whereas there was a significant positive correlation in those with a pain duration of more than 28 months. Furthermore, the resolution of chronic pain is related to recovery of the BP-related hypoalgesia (de la Coba et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bruehl et al (1998) observed a small negative correlation between BP and clinical pain severity in patients with a pain duration between 6 and 14 months, whereas there was a significant positive correlation in those with a pain duration of more than 28 months. Furthermore, the resolution of chronic pain is related to recovery of the BP-related hypoalgesia (de la Coba et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The association between hypertension and pain had been repeatedly reported in many single-center clinical studies. For instance, hypertension was correlated with lower prevalence of low back pain or osteoarthritis in Koreans [ 25 ], higher pain thresholds in participants with resolved functional abdominal pain [ 26 ], and lower chest pain scores in patients with acute myocardial infarction [ 27 ]. It is likely that hypertension was associated with lower pain scores among participants, and hence reducing the risk of MRP development.…”
Section: Discussionmentioning
confidence: 99%
“…Относительно длительности, о чем говорилось выше [18], de la Coba P. соавт. недавно показали, что со временем, если боль становится хронической, защитный механизм феномена «гипоалгезия, связанная с гипертонией» начинает ослабевать [27]. Это работает и в обратном направлении: при хроническом характере повышения АД развивается гипералгезия.…”
Section: история изучения и новые взгляды на фенотип «аг+гб»unclassified